A Four-Component Framework Toward Patient-Centered, Integrated Mental Healthcare in Kenya - Kumar, Manasi; Osborn, Thomas L.; Mugo, Cyrus; Akbarialiabad, Hossein; Warfa, Osman; Mbuthia, Wangui Muthigani; Wambugu, Christine; Ngunu, Carol; Gohar, Fatima; Mwaniga, Shillah; Njuguna, Simon; Saxena, Shekhar (Frontiers in Public Health, 2021)
Background: How can we fast-track the global agenda of integrated mental healthcare in low- and middle-income countries (LMICs) such as Kenya? This is a question that has become increasingly important for individuals with lived experiences, policymakers, mental health advocates and health care providers at the local and international levels. Discussion: This narrative synthesis and perspective piece encompasses an overview of mental health care competencies, best practices and capacity building needed to fast track patient responsive services. In that vein we also review key policy developments like UHC to make a case for fast-tracking our four-step framework. Results: While there is an increasingly global impetus for integrated mental healthcare, there is a lack of clarity around what patient-responsive mental healthcare services should look like and how to measure and improve provider readiness appropriately. Here, our collaborative team of local and international experts proposes a simple four-step approach to integrating responsive mental healthcare in Kenya. Our recommended framework prioritizes a clear understanding and demonstration of multidimensional skills by the provider. The four steps are (1) provider sensitization, (2) continuous supervision, (3) continuous professional training, and (4) leadership empowerment. Conclusion: Our proposed framework can provide pointers to embracing patient-centered and provider empowerment focused quality of care improvements. Though elements of our proposed framework are well-known, it has not been sufficiently intertwined and therefore not been integrated. We think in the current times our integrated framework offers an opportunity to “building back better” mental health for all.